An Ultralong Lifespan and Low‐Temperature Workable Sodium‐Ion Full Battery for Stationary Energy Storage. Issue 18 (12th March 2018) - Wang, Ying‐Ying; Hou, Bao‐Hua; Guo, Jin‐Zhi; Ning, Qiu‐Li; Pang, Wei‐Lin; Wang, Jiawei; Lü, Chang‐Li; Wu, Xing‐Long
Abstract: Presently, commercialization of sodium‐ion batteries (SIBs) is still hindered by the relatively poor energy‐storage performance. In addition, low‐temperature (low‐T) Na storage is another principal concern for the wide application of SIBs. Unfortunately, the Na‐transfer kinetics is extremely sluggish at low‐T, as a result, there are few reports on low‐T SIBs. Here, an advanced low‐T sodium‐ion full battery (SIFB) assembled by an anode of 3D Se/graphene composite and a high‐voltage cathode (Na3 V2 (PO4 )2 O2 F) is developed, exhibiting ultralong lifespan (over even 15 000 cycles, the capacity retention is still up to 86.3% at 1 A g −1 ), outstanding low‐T energy storage performance (e.g., all values of capacity retention are >75% after 1000 cycles at temperatures from 25 to −25 °C at 0.4 A g −1 ), and high‐energy/power properties. Such ultralong lifespan signifies that the developed sodium‐ion full battery can be used for longer than 60 years, if batteries charge/discharge once a day and 80% capacity retention is the standard of battery life. As a result, the present study not only promotes the practicability and commercialization of SIBs but also points out the new developing directions of next‐generation energy storage for wider range applications. Abstract : An outstanding anode material with superior low‐temperature Na‐storage performance is first prepared, and then an advanced sodium‐ion full battery is assembled and studied via coupling such anode with Na3 V2 (PO4 )2 O2 F cathode. The assembled full battery exhibits ultralong cycle life, superior low‐temperature, and high‐power energy‐storage performances.